Differences in Cognitive Process-Related Skills between Taxi and Non-Taxi Drivers between 50 and 70 Years Old. Issue 1 (August 2014) - Chuang, Kai-Hsiang; Jeng, Ming-Chang; Chun-Chia, Hsu; Doong, Ji-Liang; Lin, Chih-Yung; Lai, Ching-Huei
This study investigated differences between 50- to 70-yr.-old taxi and non-taxi drivers with respect to cognitive process-related skills. Psychological indicators associated with perceptuomotor, attentional, and spatial memory recall abilities were collected for 173 taxi drivers (7 women, 166 men; M age = 57.5yr.) and 175 non-taxi drivers (85 women, 90 men; M age = 58.2yr.). The taxi drivers had shorter reaction times and motor times in response to stimuli in simple stimulus-response tasks. There was an age-related decline in monocular vision detection on both sides, processing speed for fovea stimuli, and higher-level cognition for drivers. Accordingly, the frontal visual information processing speed of the taxi drivers was superior to the non-taxi drivers, but a distinct age-related decline was observed for all drivers.